Pengaruh Aplikasi Eco Enzyme dan Beberapa Varietas Tanaman Jagung Manis (Zea mays saccharata Sturt.) terhadap Peningkatan HasiI, Padatan Total Terlarut (PTT) dan Vitamin C - Andika, Alya Balqis; Hafsah, Siti; Marliah, Ainun (Vegetalika, 2025)
Sweet corn (Zea mays saccharata Sturt.) is the third largest horticulture group in Indonesia. However, the import rate is still high in Indonesia due to low domestic production. Fertilization and the use of superior varieties are efforts to increase production. However, inorganic fertilizers still dominate maize cultivation. As a result, microorganisms that should be an essential unit in the availability of plant nutrients are threatened. This research was conducted to find out the effect of eco enzyme application and several varieties of sweet corn on increasing sugar content and vitamin C in the field. In this research was used a split plot randomized group design (RGD) with 2 factors and 3 times repetition. The main plot factor in this research was 4 varieties and the subplot factor was 3 levels of eco enzyme concentration. As the results of the research is the varieties of sweet corn plants gave a significant effect on several parameters of observation. Bonanza variety produced better Total Dissolved Solids, while Paragon variety produced better growth and vitamin C characteristics. The concentration of eco enzyme didn’t give an effect on all parameters. Concentration of eco enzyme 20 mI I-1 of water gave better growth characteristics and cob weight. The concentration of eco-enzyme and sweet corn varieties has a most significant interaction on the number of cobs per plot. The best combination was Paragon variety and eco enzyme concentration of 10 mI I-1 of water which made more cobs per plot.